IoT-Enabled Automated Circuit Breaker with Password Protection for Smart Homes using Arduino and ESP8266 - Lee Kuan Pang; Mohd Fadly Abd Razak (Progress in Engineering Application and Technology, 2026)
The Internet of Things (IoT) has enabled the development of smart home systems that improve safety, monitoring, and user control of residential electrical installations. The basic protection system operates through conventional circuit breakers which protect against electrical faults but it fails to provide real-time monitoring and remote access and secure operation. This study presents the development of an IoT enabled automated circuit breaker with password protection for smart home applications. The proposed system aims to improve electrical safety through real-time monitoring, secure access control, and automatic fault protection. The system operates through an Arduino Mega 2560 microcontroller which connects to an ESP8266 Wi-Fi module and ACS712 current sensor and ZMPT101B voltage sensor and relays and keypad and LCD and Blynk mobile application. Electrical parameters such as current and voltage are continuously monitored to detect abnormal operating conditions. When predefined thresholds are exceeded, the system automatically trips the circuit and sends instant alerts to users via the Blynk platform. Experimental results demonstrate accurate current and voltage detection, fast fault response, and reliable remote monitoring and control, confirming the effectiveness of the proposed system as a smart circuit breaker solution for enhancing electrical safety in modern smart homes.